Which Presentation Speed Is Better for Learning Basketball Tactical Actions Through Video Modeling Examples? The Influence of Content Complexity - Jarraya, Mohamed; Rekik, Ghazi; Belkhir, Yosra; Chtourou, Hamdi; Nikolaidis, Pantelis T.; Rosemann, Thomas; Knechtle, Beat (Frontiers in Psychology, 2019)
The present experiment examined the effect of content complexity on perceived cognitive load and game performance when learning basketball tactical actions from videos modeling examples displayed at different speeds. A 2 (presentation speed: slow vs. normal) × 3 (content complexity: low vs. medium vs. high) between subjects design was adopted in the experiment. One hundred and twenty secondary school students were quasi-randomly assigned to six experimental conditions and required to rate their perceived cognitive and to perform a game performance following the learning phase. Data analyses revealed that for low complexity content, both speeds of presentation have similar effects on learning. Conversely, for medium and high complexity contents, participants exposed to the slow-presentation speed learned more efficiently than those exposed to the normal-presentation speed. The findings recommend the use of slow-speed videos, when learning basketball tactical actions depicted, particularly, in playing systems with medium or high levels of complexity.